1999
DOI: 10.1002/hep.510290427
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Primary Sclerosing Cholangitis Following Liver Transplantation

Abstract: Recurrence of primary sclerosing cholangitis (PSC) following liver transplantation has been suggested; however, it has not been fully defined because of numerous complicating factors and the lack of diagnostic criteria. In the present study, we investigated the recurrence of PSC by developing strict criteria and applying them to a large cohort of PSC patients who underwent liver transplantation. Between March 1985 and June 1996, 150 PSC patients underwent liver transplantation at the Mayo Clinic; mean follow u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
215
1
7

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(230 citation statements)
references
References 23 publications
7
215
1
7
Order By: Relevance
“…Similarly, histopathologic characteristics of PSC recurrence can be similar to CR. 40,41 In the present series, we observed the development of CR in 3.7% of patients (3 of 81 patients) with a primary diagnosis of PSC.…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, histopathologic characteristics of PSC recurrence can be similar to CR. 40,41 In the present series, we observed the development of CR in 3.7% of patients (3 of 81 patients) with a primary diagnosis of PSC.…”
Section: Discussionsupporting
confidence: 51%
“…This is similar to a recurrence rate of 20% reported in adults. 25 In summary, our study showed that children with PSC have a significantly shorter survival than that expected in age-and gender-matched general population. PSC follows a progressive course in children, with many patients requiring liver transplantation, but PSC may recur in the allograft.…”
Section: Discussionmentioning
confidence: 47%
“…lO Although recurrence of PBC and PSC was initially the source of much debate, numerous studies subsequently have described its occurrence and natural hist 0 r y .~~,~3 A recent analysis from the Mayo Clinic found evidence of PSC recurrence in 20% of liver transplant recipients. 24 In another report, 13 of 83 liver transplant recipients with PBC developed allograft findings consistent with PBC versus none of 105 patients who underwent transplantation for causes other than PBC. 25 In each series, a small proportion (<5%) ultimately developed graft failure caused by recurrent PBC or PSC.…”
Section: Indications For Re-oltmentioning
confidence: 97%